2017
DOI: 10.1093/europace/euw232
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between oesophageal heating during left atrial posterior wall ablation and the durability of pulmonary vein isolation

Abstract: Pulmonary vein reconnections are predominantly posteriorly located. Along the right- and left-inferior PW segments, there was an association with elevated oesophageal temperature during the index procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Another important finding was the independence of recurrence rates of AF after ablation from the esophageal position or temperature. A much smaller study by Tran et al found that pulmonary vein reconnection was increased in the region of the inferior but not the superior veins, when the esophageal temperature had risen in the index procedure. As described, neither esophagus localization nor esophagus temperature influenced recurrence rates.…”
Section: Discussionmentioning
confidence: 95%
“…Another important finding was the independence of recurrence rates of AF after ablation from the esophageal position or temperature. A much smaller study by Tran et al found that pulmonary vein reconnection was increased in the region of the inferior but not the superior veins, when the esophageal temperature had risen in the index procedure. As described, neither esophagus localization nor esophagus temperature influenced recurrence rates.…”
Section: Discussionmentioning
confidence: 95%
“…The risk is present with standard PV circumferential ablation with no evidence to suggest that PWI increases this risk. In accordance with the 2017 HRS guidelines, an esophageal temperature probe is recommended, although recent evidence suggests that it may lead to increased reconnection at sites of increased temp recordings …”
Section: Discussionmentioning
confidence: 99%
“…Methods to prevent injury should be utilized such as temperature monitoring, power reduction, esophageal deviation or active esophageal cooling. We currently utilize temperature probe monitoring and power reduction although no strong evidence exists that monitoring reduces AEF formation and it could result in impaired lesion formation through operator changes in lesion delivery 20 . Esophageal cooling could be a promising alternative and is actively being investigated.…”
Section: Coronary Sinus Isolationmentioning
confidence: 99%